ANALISIS FAKTOR-FAKTOR PENGHAMBAT GURU DALAM PELAKSANAAN PEMBELAJARAN GEOGRAFI KELAS X DI SMA NEGERI 1 INDRALAYA - Sigit Prasetyo; Houtman Houtman; Boby Agus Yusmiono (Jurusan Geografi Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
This study aims to uncover factors that inhibit teachers in the implementation of class X geography learning in 1 Senior High School of Indralaya. This study uses a qualitative approach. The object of this research is class X geography learning at 1 Senior High School of Indralaya The subjects of this study were the Principal, geography teacher, and class X students of SMA Negeri 1 Indralaya. Data collection is done by interview, observation and documentation. Data analysis techniques used are a) data reduction, b) data presentation, and c) conclusion making. Test the validity of the data using triangulation techniques. based on the results of the study found three main factors that become obstacles in the implementation of geography learning in class X SMA Negeri 1 Indralaya namely; 1) teacher factor, 2) infrastructure facilities factor, and 3) learning process factor. Furthermore, from the results of the study found, that the efforts made by teachers to overcome the problem of learning there has not been a significant impact on improving the quality of learning geography in class X SMA Negeri 1 Indralaya